Impact of CYP2C19 polymorphism in prognosis of minor stroke or TIA patients with declined eGFR on dual antiplatelet therapy: CHANCE substudy. Issue 6 (December 2018) - Wu, Yu; Zhou, Yilun; Pan, Yuesong; Zhao, Xingquan; Liu, Liping; Wang, David; Wang, Chunxue; Li, Hao; Johnston, S.; Meng, Xia; Wang, Yilong; Wang, Yongjun
Abstract Clopidogrel resistance is prevalent in chronic kidney disease (CKD) patients. Genetic polymorphism is considered to be the most important factor that influences clopidogrel resistance. Limited data exist as to the role of pharmacogenetics in prognosis of stroke patients with impaired renal function on clopidogrel. We sought to explore whether decreased kidney function alters the association between CYP2C19 genetic variants and clinical outcome in patients with minor stroke or transient ischemic attack (TIA) receiving clopidogrel therapy. A total of 1476 participants on clopidogrel-aspirin treatment with genotyping results in High-Risk Patients with Acute Nondisabling Cerebrovascular Events (CHANCE) trial were categorized by quintiles of renal function estimated by estimated glomerular filtration rate (eGFR), and were stratified according to the possession of CYP2C19 loss-of-function (LOF) alleles: carriers and non-carriers. Patients were followed up and clinical outcomes were evaluated. The primary efficacy outcome was new stroke. The secondary efficacy outcome was combined vascular events (ischemic stroke, hemorrhagic stroke, myocardial infarction, or vascular death). The safety outcome was bleeding event. CYP2C19 LOF carriers had higher odds of new stroke than non-carriers (10.4% versus 2.4 %, hazard ratio [HR], 5.30; 95% CI, 1.51–18.3, P  = 0.009) in the lowest quintile of renal function group with eGFR < 75 ml/min/1.73 m2 but not in the other four higher quintiles. Similar results were observed for the ischemic stroke and combined vascular events. There was no significant difference in the individual outcomes of bleeding in carriers compared with non-carriers in any renal function group. Among patients with minor stroke or TIA taking clopidogrel-aspirin treatment, CYP2C19 LOF carrier state was associated with higher risk of new stroke in those with eGFR < 75 ml/min/1.73 m2 . This observation supports that the evaluation of CYP2C19 LOF carrier state may be useful for identification of the patients with kidney impairment with greater likelihood of having worse outcomes.